2008
DOI: 10.1097/yct.0b013e318157ac58
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Electroconvulsive Therapy in Treatment-Resistant Depression

Abstract: The ECT is still highly effective in severely treatment-resistant patients with major depressive disorder, with more than half of such patients achieving remission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 20 publications
2
25
0
5
Order By: Relevance
“…This indicates a possible general sex effect or may be the result of fewer antidepressant drug trials in women before being referred to ECT as reported by Bloch and colleagues 33 that may result in better treatment response. 34 The number of concomitant psychotropic medications and the degree of treatment resistance to various pharmacological treatments showed no significant variation over age. Our patients can in fact be considered as a population experiencing extremely high pharmacotherapy-resistant illness, 35 having failed in up to 20 different treatment trials, including augmentation and combination strategies before ECT.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates a possible general sex effect or may be the result of fewer antidepressant drug trials in women before being referred to ECT as reported by Bloch and colleagues 33 that may result in better treatment response. 34 The number of concomitant psychotropic medications and the degree of treatment resistance to various pharmacological treatments showed no significant variation over age. Our patients can in fact be considered as a population experiencing extremely high pharmacotherapy-resistant illness, 35 having failed in up to 20 different treatment trials, including augmentation and combination strategies before ECT.…”
Section: Discussionmentioning
confidence: 99%
“…the treatment of choice for patients whose symptoms fail to remit with the use of psychopharmacology, who have depression with severe psychosis, who are experiencing an unrelenting lethal suicidal threat, or who have a medical condition that prohibits the use of psychotropic medication (Khalid et al 2008). Patients with schizophrenia, mania, delusions, catatonia, neuroleptic malignant syndrome, and Parkinsonism also have had positive responses to ECT (Greenberg & Kellner, 2005;Tharyan & Adams, 2005).…”
mentioning
confidence: 99%
“…Electroconvulsive therapy (ECT) is an effective anti-depressive therapy that is most commonly reserved for severe treatment resistant depression [10]. No previous study has assessed baroreflex function among patients undergoing electro-convulsive therapy in adjunct to medical therapy for major depressive disorder.…”
Section: Introductionmentioning
confidence: 99%